2017
DOI: 10.1038/s41598-017-16940-y
|View full text |Cite
|
Sign up to set email alerts
|

The potential therapeutic effect of melatonin on human ovarian cancer by inhibition of invasion and migration of cancer stem cells

Abstract: There is an urgent need to identify targeting molecules to control invasion and metastasis in cancer patients. We first isolated cancer stem cells (CSCs) from SKOV3 ovarian cancer cells and then investigated the role of melatonin in invasiveness and migration of CSCs compared to SKOV3 cells. The proportion of CSCs in SKOV3 cells was as low as 1.28% with overexpression of both CD133 and CD44. The ability of spheroid formation along with SOX2 overexpression revealed a high self-renewal potential in isolated cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 51 publications
2
55
1
Order By: Relevance
“…We showed elevated levels of NANOG transcripts in GLC incubated with 10 nmol/L MEL, which is contrary to recent findings in ovarian cancer stem cells [9], but in line with other reports showing enhanced expression of c-Myc and Nanog after MEL treatment [24]. Up-regulation of NANOG expression by MEL in nontumour ovarian GLC as demonstrated in the present study points out at the balancing role of the circadian hormone in a physiological context depending on cell type, period of exposure and dose applied.…”
Section: Expression Of Klf4 Myc and Nanogcontrasting
confidence: 99%
See 1 more Smart Citation
“…We showed elevated levels of NANOG transcripts in GLC incubated with 10 nmol/L MEL, which is contrary to recent findings in ovarian cancer stem cells [9], but in line with other reports showing enhanced expression of c-Myc and Nanog after MEL treatment [24]. Up-regulation of NANOG expression by MEL in nontumour ovarian GLC as demonstrated in the present study points out at the balancing role of the circadian hormone in a physiological context depending on cell type, period of exposure and dose applied.…”
Section: Expression Of Klf4 Myc and Nanogcontrasting
confidence: 99%
“…Other data indicated that MEL increased the efficiency of reprogramming both by somatic cell nuclear transfer (SCNT) [7] and by direct induction of pluripotent stem cells (iPSC) [8]. MEL was shown also to influence the pluripotency, proliferation and invasion properties of ovarian cancer stem cells by reducing the expression of SOX2 and NANOG [9]. However, the precise action of the pineal hormone in cancer stem cells is yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of the insignificant reduction of CD44 expression in contrary to a study by Goncalves, Kocak, and Akbarzadeh, presumably due to the use of cell culture instead of a tissue sample, thus permitting better control to confounding factors and requiring different examination techniques of CD44 [24][25][26]. A study by Ullman mentioned a link between miR-210 and regulation of CD44; thus, the reduction of CD44 in this study may come as a result from the decrease of miR-210 [27].…”
Section: Discussionmentioning
confidence: 84%
“…The metastatic activity of oral squamous cell carcinoma was notably reduced by melatonin-mediated inhibition of tumor-associated neutrophils [82], inflammatory cells involved in promoting several solid tumors [83]. Similarly, the anti-oncogenic property of melatonin has been demonstrated also in other cancer types, including lung [84], gastric [85], ovarian [86], and colon [87], as well as breast cancers [88].…”
Section: Melatonin As a Mediating Signal Linking Alan And Epigenetic-mentioning
confidence: 99%